Impact of mixing time and energy on the dispersion effectiveness and droplets size of oil. (January 2017) - Pan, Zhong; Zhao, Lin; Boufadel, Michel C.; King, Thomas; Robinson, Brian; Conmy, Robyn; Lee, Kenneth
Abstract: The effects of mixing time and energy on Alaska Northern Slope (ANS) and diluted bitumen Cold Lake Blend (CLB) were investigated using EPA baffled flask test. Dispersion effectiveness and droplet size distribution were measured after 5–120 min. A modeling method to predict the mean droplet size was introduced for the first time to tentatively elucidate the droplet size breakup mechanism. The ANS dispersion effectiveness greatly increased with dispersant and mixing energy. However, little CLB dispersion was noted at small energy input ( ε  = 0.02 Watt/kg). With dispersant, the ANS droplet size distribution reached quasi-equilibrium within 10 min, but that of CLB seems to reach quasi-equilibrium after 120 min. Dispersants are assumed ineffective on high viscosity oils because dispersants do not penetrate them. We provide an alternative explanation based on the elongation time of the droplets and its residence in high intensity zones. When mixing energy is small, CLB did not disperse after 120 min, long enough to allow the surfactant penetration. Our findings suggest that dispersants may disperse high viscosity oils at a rougher sea state and a longer time. The latter could determine how far offshore one can intervene for effective responses to a high viscosity oil spill offshore. Highlights: The effects of mixing time and energy on the oil dispersion were compared. A droplet size modeling was first introduced for the droplet breakup mechanism. The dispersion was explained using the elongation time of the droplets. Dispersants may work on high viscosity oils in a rougher sea state and a longer time.